2020
DOI: 10.1177/1535370220966253
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA IGF2-AS represses breast cancer tumorigenesis by epigenetically regulating IGF2

Abstract: Long non-coding RNAs are a kind of endogenous ncRNAs with a length of more than 200 bp. Accumulating evidence suggests that long non-coding RNAs function as pivotal regulators in tumorigenesis and progression. However, their biological roles in breast cancer remain largely unknown. Here, we found that IGF2 antisense RNA (IGF2-AS) was significantly decreased in breast cancer tissues, cell lines, and plasma. Patients with low IGF2-AS were more likely to develop larger tumor size and later clinical stage. Overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Collectively, these results indicated that IGF2-AS may serve as a tumor suppressor in HCC, a potential prognostic biomarker and therapeutic target for HCC patients. Our findings are in line with what have been reported in several other cancers including breast cancer [6], gastric cancer [7], CRC [8], and gastric adenocarcinoma [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Collectively, these results indicated that IGF2-AS may serve as a tumor suppressor in HCC, a potential prognostic biomarker and therapeutic target for HCC patients. Our findings are in line with what have been reported in several other cancers including breast cancer [6], gastric cancer [7], CRC [8], and gastric adenocarcinoma [22].…”
Section: Discussionsupporting
confidence: 93%
“…Increasing studies have verified that long noncoding RNAs (lncRNAs) play key roles during the development of multiple human cancers [ 3–5 ]. Studies have reported that IGF2-AS is a biomarker for cancer diagnosis and prognosis, including as a tumor suppressor in breast cancer [ 6 ], a promotor of glycolysis and apoptosis of gastric cancer cells via targeting miR-195/CREB1 axis [ 7 ], a potential target for colorectal cancer (CRC) treatment [ 8 ], as well as the prognosis and metastasis of gastric adenocarcinoma via serving as a ceRNA of miR-503 to regulate SHOX2 9 . We identified that IGF2-AS was remarkably down-regulated in tumor tissues by analyzing the differentially expressed lncRNAs in HCC based on the RNA-seq dataset in TCGA database (14 tumor and 42 adjacent normal samples) ( Figure 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…Some published results showed that some lncRNAs play an important regulatory role in the tumorigenesis of some cancers such as breast cancer, ovarian cancer, cervical cancer and so on. For example, the lncRNA IGF2-AS, as an antisense gene of IGF2, inhibits the tumorigenesis of breast cancer by epigenetically regulating IGF2 and affects the metastasis and prognosis of gastric adenocarcinoma by sponging miR-503 to regulate SHOX2 [28,29]. The lncRNA EMX2OS has been reported to affect the proliferation and invasion of ovarian cancer cells by sponging miR-654-3p to regulate AKT3 and the downregulation of EMX2OS results in a poor prognosis of patients with kidney renal clear cell carcinoma [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, lncRNA IGF2‐AS was extensively studied in human cancers 16 . Functionally, IGF2‐AS represses breast cancer tumorigenesis by epigenetically regulating IGF2 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, lncRNA IGF2‐AS was extensively studied in human cancers 16 . Functionally, IGF2‐AS represses breast cancer tumorigenesis by epigenetically regulating IGF2 16 . Moreover, IGF2‐AS regulates high‐glucose‐induced apoptosis in human retinal pigment epithelial cells 17 .…”
Section: Introductionmentioning
confidence: 99%